Introduction to security - Fischer, Robert (Elsevier, 2013)
Introduction to Security has been the leading text on private security for over thirty years. Celebrated for its balanced and professional approach, this new edition gives future security professionals a broad, solid base that prepares them to serve in a variety of positions in a growing field that is immune to outsourcing. Former and current members of the military, as well as works displaced by disappearing jobs, can all benefit from reading this book. The author team as well as an outstanding group of subject-matter experts combine knowledge and experience to create content geared to experiential learning. As a recommended title for security certifications, it is a crucial resource for working professionals, and is also used as a core security textbook in universities throughout the country. This is Butterworth-Heinemann's best-selling security text of all time, an essential reference for all security professionals. The 9th edition expands on key topics and adds new material on the important issues in the 21st century environment such as: the importance of communication skills; the value of education; internet-related security risks; changing business paradigms; and brand protection. New sections on terrorism and emerging security threats like cybercrime and piracy. Top industry professionals from aerospace and computer firms join instructors from large academic programs as co-authors and contributors. Expanded ancillaries for both instructors and students, including interactive web-based video and case studies.